If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -8b + 6 + -2b = 0 Reorder the terms: 5 + 6 + -8b + -2b = 0 Combine like terms: 5 + 6 = 11 11 + -8b + -2b = 0 Combine like terms: -8b + -2b = -10b 11 + -10b = 0 Solving 11 + -10b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -10b = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -10b = 0 + -11 -10b = 0 + -11 Combine like terms: 0 + -11 = -11 -10b = -11 Divide each side by '-10'. b = 1.1 Simplifying b = 1.1
| 15x+40=8x-9 | | -33=-x+7x-3 | | h=6t^2+112t+1248 | | -2y^2+16y-x-28=0 | | -2(8t^2-48t-8)=0 | | X^3+4x=80 | | 47.75=5(2.95+x) | | 3(2x+5)-x=-5x-15 | | 3x=27.9 | | 4a^2-7a-2=0 | | x+(4x)=5 | | (2t^2-t-15)/(3t^2-8t-3) | | 3(2x+5)-x=4x+15 | | 6m^2=13m+38 | | =5+7(0)+4 | | ln(x)=1/9 | | y=-4/3x^2-8x | | -3x-23=3x+19 | | 7-4x-6x=-3 | | 2x+(1-x)=7 | | x+(x+1.3)+(x-1.3)=27.9 | | 3(2x+5)-x=15x+5 | | 225=50t | | x-1(x+7)=500 | | 1+4=2+3 | | 6m^2-5m-6=0 | | 3(2x+5)-x=-5x+10 | | y=-3x-23 | | 12-4=3+6 | | 2q+397=813 | | 3(2x+5)-x=-4x+15 | | 19=n+11 |